Bloodstream infections during post-cardiotomy extracorporeal membrane oxygenation: Incidence, risk factors, and outcomes. Issue 6 (June 2019) - Silvetti, Simona; Ranucci, Marco; Pistuddi, Valeria; Isgrò, Giuseppe; Ballotta, Andrea; Ferraris, Laurenzia; Cotza, Mauro
Introduction: Veno-arterial extracorporeal membrane oxygenation after heart surgery is a relatively common procedure. It is easily applicable but associated with a number of complications, including bloodstream infections. The aim of this study is to determine the current rate and the risk factors related to bloodstream infections acquired during post-cardiotomy veno-arterial extracorporeal membrane oxygenation. Methods: Single-center retrospective study. From the overall population receiving any kind of extracorporeal membrane oxygenation from March 2013 through December 2017, the post-cardiotomy patient population was extracted, with a final sample of 92 veno-arterial extracorporeal membrane oxygenations. The risk of developing bloodstream infections as a function of extracorporeal membrane oxygenation exposure was analyzed with appropriate statistical analyses, including a Kaplan–Meier analysis. Results: Overall, 14 (15.2%) patients developed a bloodstream infection during extracorporeal membrane oxygenation or within the first 48 h after extracorporeal membrane oxygenation removal. The total extracorporeal membrane oxygenation duration in the population was 567 days, and the incidence of bloodstream infections was 24.7 bloodstream infections/1000 extracorporeal membrane oxygenation days. There was a progressive increase in the cumulative hazard ratio during the first 7 days, reaching a value of 20% on day 7; from day 7 and day 15, the hazard ratio remained stable, with a second increase after day 15. The independent risk factors associated with bloodstream infections were adult age, pre-implantation serum total bilirubin level, and the amount of chest drain blood loss. Discussion: Infections acquired during veno-arterial extracorporeal membrane oxygenation are common. Identify the risk factors that may improve strategies for treatment and prevention.